The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00464-017-5453-9
|View full text |Cite
|
Sign up to set email alerts
|

Prior experience in laparoscopic rectal surgery can minimise the learning curve for robotic rectal resections: a cumulative sum analysis

Abstract: For experienced laparoscopic colorectal surgeons, the formal learning process for robotic TME may be short to reach a similar performance level as obtained in conventional laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 23 publications
2
51
0
2
Order By: Relevance
“…The surgeon's previous experience may have been a significant factor; in three of five studies comparing the operating time learning curves of robotic surgeons, those with greater experience required fewer procedures to overcome their learning curve 16,29,38 . Although the captured studies often compared surgeons with different experience levels, such as trainees versus those who had completed training or robotic versus laparoscopic surgeons, studies generally did not report the participants' specific grade or training experience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The surgeon's previous experience may have been a significant factor; in three of five studies comparing the operating time learning curves of robotic surgeons, those with greater experience required fewer procedures to overcome their learning curve 16,29,38 . Although the captured studies often compared surgeons with different experience levels, such as trainees versus those who had completed training or robotic versus laparoscopic surgeons, studies generally did not report the participants' specific grade or training experience.…”
Section: Discussionmentioning
confidence: 99%
“…These were sometimes based on the performance of expert robotic surgeons 50 , whereas others 38,56 included expert laparoscopic surgeons. A large proportion of studies measured the number of procedures required to reach a plateau in surgeon performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of the cumulative sum methodology to evaluate the learning process of RALS for rectal cancer has been reported. To date, nine studies have reported the learning curve of RALS for rectal cancer using the cumulative sum method, providing a range of 15–44 cases for the learning period . Conversely, previous studies that focused on the learning curve of laparoscopic rectal surgery estimated that approximately 40–90 cases are required to attain proficiency .…”
Section: Learning Curvementioning
confidence: 99%